The Deployed Military Orthopaedic Surgeon: Experiences of a Recent Iowa Graduate in Afghanistan - Malin, Andrew S. (The University of Iowa, 2012)
Orthopaedic surgeons deployed to Afghanistan are primarily responsible for the provision of care to injured Us and coalition soldiers. A vast and well-coordinated system of echeloned care has evolved to rapidly treat and evacuate injured soldiers. Orthopaedic care of injured Afghan civilians represents a common secondary mission performed by deployed orthopaedic surgeons. In this article, I describe my experiences while deployed to Afghanistan in 2011 as part of the special Operations surgical team.